Using Spot Dictation to Improve the First Semester Students’ Vocabulary Mastery at Stkip Pgri Tulungagung - Ika Rakhmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
Being able to read in English is very important as it is known that success in reading is the most necessary because it is a basic tool of education. Consequently, the concern of English learning is no longer on the acquisition of language components i.e. grammar, vocabulary, and sound system in isolation. Rather, it is targeted at the students learning and analyzing the whole text, at how it is constructed to achieve its purpose (Carrell, 1996: 26). The design of this research is a classroom action research with cycle model since this research is planned to improve the students’ Vocabulary Mastery at the second semester of STKIP PGRI Tulungagung using Spot Dictation. Action research is a form of collective self-reflective enquiry undertaken by participants in social situations in order to improve the rationality and justice of their own social or educational practices, as well as their understanding of those practices and the situations in which the practices are carried out (Carr and Kemmis 1988: 5-6 in Smith, 2007). According to the result of Test Cycle I was done in cycle I, it was found that the students who could reach the passing grade were 21 students (84%) and 4 students (16%) were failed. The criteria of success which had been determined was 80% of the students and the standard value was 80. So, the action in cycle 1 was successful. The suggestion for the students by using Spot Dictation, the students can know much Vocabulary Mastery and it makes students more active in teaching and learning process, for English lecturer should use Spot Dictation as alternative way in teaching Vocabulary Mastery and for future researcher as the reference to make a further research.